Risk Assessment of Soil Heavy Metals in the Jiahe River Basin of Yantai City, China - Xizhuo Chen; Pengfei Zhao; Jiaxin Huang; Jun Liu; Xiaoli Cao; Jing Che; Hui Liao; Xiaolong Zhu; Qingjie Gong (Applied Sciences)
The issues related to soil environmental contamination caused by heavy metals have garnered increasing attention. In particular, the soil pollution risk in the eastern coastal regions of China has attracted widespread concern. This study surveyed heavy metals in the soils near the Jiahe River Basin of Yantai City in Shandong Province, China. A total of 213 soils were sampled and analyzed for 12 items: Cr, Hg, As, Pb, Cd, Cu, Ni, Zn, Co, V, Mn, and pH. The 11 heavy metals were evaluated using the national standard GB15618-2018, with three risk levels of background, screening, and intervention, and using pollution indices, including the contamination factor (Cf), ecological risk factor (Er), enrichment factor (EF), and index of geo-accumulation (Igeo), with different respective risk levels. The results indicate a strong consistency between the evaluations both for the index Igeo and for GB15618-2018 on five metals (i.e., Cr, Hg, As, Pb, and Cd). Therefore, the index Igeo may serve as a supplementary indicator for assessing the pollution risks of heavy metals in agricultural soils regarding samples of Cu, Ni, and Zn that exceed the screening values in GB15618-2018, as well as for Co, V, and Mn, which have not yet been established in GB15618-2018. According to the three-level classification of risk in GB15618-2018, the seven commonly used levels of the index Igeo are also incorporated into the three levels of background, screening, and intervention. The overall pollution risk of 11 heavy metals in the soils of the Jiahe River Basin of Yantai City belongs to the background level. Specifically, Hg and Pb in the total area are classified at the background level. Manganese, V, Co, Zn, Ni, and Cr are recognized at the screening level sporadically, while Cu, As, and Cd are found at the screening level in small areas. No areas within the region are classified at the intervention level.